Towards a common metric for assessing heroin-dependent patient satisfaction with medications: Testing methadone and buprenorphine-naloxone - Pérez de los Cobos, José; Alcaraz, Saul; Sinol, Nuria; González-Saiz, Francisco; Vergara-Moragues, Esperanza (Drug and Alcohol Dependence, 2020)
Background: Patient satisfaction with methadone or buprenorphine-naloxone can be multidimensionally and specifically assessed by using, respectively, the Scale to Assess Satisfaction with Medications for Addiction Treatment–Methadone for Heroin addiction (SASMAT-METHER) or the SASMAT–Buprenorphine-Naloxone for Heroin addiction (SASMAT-BUNHER). The factor structures of the SASMAT-METHER and SASMAT-BUNHER show substantial commonalities. The objective of the present study is to evaluate the replicability of the SASMAT-METHER factor structure using data from the SASMAT-BUNHER development study in order to obtain an instrument that can be used to compare patient satisfaction with methadone vs. buprenorphine-naloxone. Method: Secondary analysis of SASMAT-BUNHER data provided by 205 participants in the original validation study of that scale (Pérez de los Cobos et al., 2018). Using the SASMAT-METHER component solution (17 items, 3 factors) as the target structure, a principal component analysis was performed on the data set comprised of the corresponding 17 SASMAT-BUNHER items using an oblique semi-specified Procrustean rotation. Additionally, Tucker congruence coefficients were computed to examine the correspondence between the two solutions. Result: The factor structures of SASMAT-METHER and the 17-item version of the SASMAT-BUNHER can be considered equal given that the overall Tucker's congruence coefficient of factorial similarity was 0.972, with individual component congruencies ranging from 0.960 to 0.995. Conclusions: The SASMAT-METHER component solution can serve as a single common tool to compare methadone vs. buprenorphine-naloxone in terms of patient satisfaction. This finding supports the feasibility of using a common metric to specifically assess satisfaction with medications to treat heroin dependence.
Keywords: patient satisfaction; opioid; factor structure; replicability; methadone; buprenorphine-naloxone; Scopus; JCR